Role of Grb7 Targeting to Focal Contacts and Its Phosphorylation by Focal Adhesion Kinase in Regulation of Cell Migration - Dong Cho Han; Tang‐Long Shen; Jun‐Lin Guan (2000)
We have previously described Grb7 association with focal adhesion kinase (FAK) and its possible roles in cell migration. In this paper, we investigated the mechanisms by which Grb7 and its association with FAK regulate cell migration. We found that deletion of the Grb7 SH2 domain eliminated partial Grb7 localization to focal contacts and its ability to stimulate cell migration. Replacement of the SH2 domain with the focal adhesion targeting sequence from FAK resulted in the focal contacts localization of the chimeric molecule and restored its activity to stimulate cell migration. We also found that Grb7 could be phosphorylated by FAK, which was dependent on the FAK kinase activity but not the presence of the Src family kinases. Cell adhesion also enhanced Grb7 phosphorylation in FAK+/+ cells but not FAK−/− cells, suggesting that Grb7 is a physiological substrate of FAK. Furthermore, both Grb7 and the chimeric molecule did not increase migration of FAK−/− cells, although the chimeric molecule was targeted to the focal contacts. Last, we showed that other Grb7 family members could not stimulate cell migration under similar experimental conditions. Together, these results demonstrate a role for Grb7 targeting to focal contacts and its phosphorylation by FAK in the regulation of cell migration. We have previously described Grb7 association with focal adhesion kinase (FAK) and its possible roles in cell migration. In this paper, we investigated the mechanisms by which Grb7 and its association with FAK regulate cell migration. We found that deletion of the Grb7 SH2 domain eliminated partial Grb7 localization to focal contacts and its ability to stimulate cell migration. Replacement of the SH2 domain with the focal adhesion targeting sequence from FAK resulted in the focal contacts localization of the chimeric molecule and restored its activity to stimulate cell migration. We also found that Grb7 could be phosphorylated by FAK, which was dependent on the FAK kinase activity but not the presence of the Src family kinases. Cell adhesion also enhanced Grb7 phosphorylation in FAK+/+ cells but not FAK−/− cells, suggesting that Grb7 is a physiological substrate of FAK. Furthermore, both Grb7 and the chimeric molecule did not increase migration of FAK−/− cells, although the chimeric molecule was targeted to the focal contacts. Last, we showed that other Grb7 family members could not stimulate cell migration under similar experimental conditions. Together, these results demonstrate a role for Grb7 targeting to focal contacts and its phosphorylation by FAK in the regulation of cell migration. focal adhesion kinase green fluorescence protein Src homology 2 hemagglutinin Chinese hamster ovary focal adhesion-targeting Cell migration is crucial for biological processes such as embryonic development, inflammatory immune response, wound healing, and tumor metastasis. Cell migration is a multistep process that is regulated by contractile forces and cellular interactions with the extracellular matrix (1Lauffenburger D.A. Horwitz A.F. Cell. 1996; 84: 359-369Abstract Full Text Full Text PDF PubMed Scopus (3291) Google Scholar, 2Liotta L.A. Steeg P.S. Stetler-Stevenson W.G. Cell. 1991; 64: 327-336Abstract Full Text PDF PubMed Scopus (2644) Google Scholar, 3Schwartz M.A. Schaller M.D. Ginsberg M.H. Annu. Rev. Cell Dev. Biol. 1995; 11: 549-599Crossref PubMed Scopus (1474) Google Scholar, 4Clark E.A. Brugge J.S. Science. 1995; 268: 233-239Crossref PubMed Scopus (2822) Google Scholar, 5Guan J.-L. Int. J. Biochem. Cell Biol. 1997; 29: 1085-1096Crossref PubMed Scopus (280) Google Scholar). Focal adhesion kinase (FAK)1 is a cytoplasmic tyrosine kinase that is localized to focal contacts. Activation of FAK by integrin-mediated cell adhesion to extracellular matrix induces its autophosphorylation at Tyr-397, which has been shown to be a binding site for several intracellular signaling molecules including Src family kinases (6Xing Z. Chen H.-C. Nowlen J.K. Taylor S. Shalloway D. Guan J.-L Mol. Biol. Cell. 1994; 5: 413-421Crossref PubMed Scopus (285) Google Scholar, 7Cobb B.S. Schaller M.D. Leu T.-H. Parsons J.T. Mol. Cell. Biol. 1994; 14: 147-155Crossref PubMed Scopus (486) Google Scholar, 8Schaller M.D. Hildebrand J.D. Shannon J.D. Fox J.X. Vines R.R. Parsons J.T. Mol. Cell. Biol. 1994; 14: 1680-1688Crossref PubMed Scopus (1121) Google Scholar, 9Chan P.-Y. Kanner S.B. Whitney G. Aruffo A. J. Biol. Chem. 1994; 269: 20567-20574Abstract Full Text PDF PubMed Google Scholar), phosphatidylinositol 3-kinase (10Chen H.-C. Guan J.-L. Proc. Natl. Acad. Sci. U. S. A. 1994; 91: 10148-10152Crossref PubMed Scopus (478) Google Scholar), phospholipase Cγ (11Zhang X. Chattopadhyay A. Ji Q.-S. Owen J.D. Ruest P.J. Carpenter G. Hanks S.K. Proc. Natl. Acad. Sci. U. S. A. 1999; 96: 9021-9026Crossref PubMed Scopus (158) Google Scholar), and Grb7 (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar). The formation of FAK-Src kinase complexes allows phosphorylation of additional sites on FAK, including Tyr-925 for binding of Grb2 (13Schlaepfer D.D. Hanks S.K. Hunter T. van der Geer P. Nature. 1994; 372: 786-791Crossref PubMed Scopus (1448) Google Scholar, 14Schlaepfer D.D. Hunter T. Mol. Cell. Biol. 1996; 16: 5623-5633Crossref PubMed Scopus (401) Google Scholar), as well as other cellular proteins such as p130 cas and paxillin (15Turner C.E. Miller J. J. Cell Sci. 1994; 107: 1583-1591Crossref PubMed Google Scholar, 16Schaller M.D. Parsons J.T. Mol. Cell. Biol. 1995; 15: 2635-2645Crossref PubMed Scopus (502) Google Scholar, 17Vuori K. Hirai H. Aizawa S. Ruoslahti E. Mol. Cell. Biol. 1996; 16: 2606-2613Crossref PubMed Google Scholar, 18Schlaepfer D.D. Broome M.A. Hunter T. Mol. Cell. Biol. 1997; 17: 1702-1713Crossref PubMed Scopus (404) Google Scholar). FAK has been shown to play an important role in integrin-mediated signal transduction and cell migration. Inhibition of endogenous FAK by microinjection of the carboxyl-terminal segment of FAK decreased cell migration (19Gilmore A.P. Romer L.H. Mol. Biol. Cell. 1996; 7: 1209-1224Crossref PubMed Scopus (462) Google Scholar). Fibroblast derived from FAK null mice also showed markedly reduced cell motility in vitro (20Ilic D. Furuta Y. Kanazawa S. Takeda N. Sobue K. Nakatsuji N. Nomura S. Fujimoto J. Okada M. Yamamoto T. Aizawa S. Nature. 1995; 377: 539-544Crossref PubMed Scopus (1591) Google Scholar). Similarly, we have reported that stable overexpression of FAK in CHO cells stimulated cell migration and mutation of Tyr-397 to Phe abolished its ability to promote cell migration, demonstrating the importance of phosphorylation at Tyr-397 (21Cary L.A. Chang J. Guan J.-L. J. Cell Sci. 1996; 109: 1787-1794Crossref PubMed Google Scholar). Grb7 is a member of an emerging family of SH2 domain-containing adaptor molecules that include Grb7, Grb10, and Grb14 (22Margolis B. Silvennoinen O. Comoglio F. Roonprapunt C. Skolnik E. Ullrich A. Schlessinger J. Proc. Natl. Acad. Sci. U. S. A. 1992; 89: 8894-8898Crossref PubMed Scopus (150) Google Scholar, 23Ooi J. Yajnik V. Immanuel D. Gordon M. Moskow J.J. Buchberg A.M. Margolis B. Oncogene. 1995; 10: 1621-1630PubMed Google Scholar, 24Daly R.J. Sanderson G.M. Janes P.W. Sutherland R.L. J. Biol. Chem. 1996; 271: 12502-12510Abstract Full Text Full Text PDF PubMed Scopus (105) Google Scholar, 25Frantz J.D. Giorgetti-Peraldi S. Ottinger E.A. Shoelson S.E. J. Biol. Chem. 1997; 272: 2659-2667Abstract Full Text Full Text PDF PubMed Scopus (101) Google Scholar). Northern blot analysis revealed distinct expression profiles of Grb7 family molecules in different human tissues (24Daly R.J. Sanderson G.M. Janes P.W. Sutherland R.L. J. Biol. Chem. 1996; 271: 12502-12510Abstract Full Text Full Text PDF PubMed Scopus (105) Google Scholar, 25Frantz J.D. Giorgetti-Peraldi S. Ottinger E.A. Shoelson S.E. J. Biol. Chem. 1997; 272: 2659-2667Abstract Full Text Full Text PDF PubMed Scopus (101) Google Scholar). The family members share a highly conserved molecular architecture: an NH2-terminal region containing proline-rich motifs, a central region with homology to theCaenorhabditis elegans protein Mig-10 and also containing a PH domain, and a COOH-terminal SH2 domain. Grb7 family proteins have been shown to interact with a variety of other cellular proteins including tyrosine kinase receptors and protooncogenes (26Stein D. Wu J. Fuqua S.A.W. Roonprapunt C. Yajnik V. D'Eustachio P. Moskow J.J. Buchberg A.M. Osborne C.K. Margolis B. EMBO J. 1994; 13: 1331-1340Crossref PubMed Scopus (220) Google Scholar, 27Janes P.W. Lackmann M. Church W.B. Sanderson G.M. Sutherland R.L. Daly R.J. J. Biol. Chem. 1997; 272: 8490-8497Abstract Full Text Full Text PDF PubMed Scopus (72) Google Scholar, 28Yokote K. Margolis B. Heldin C.H. Claesson-Welsh L. J. Biol. Chem. 1996; 271: 30942-30949Abstract Full Text Full Text PDF PubMed Scopus (62) Google Scholar, 29Fiddes R.J. Campbell D.H. Janes P.W. Silvertsen S.P. Sasaki H. Wallasch C. Daly R.J. J. Biol. Chem. 1998; 273: 7717-7724Abstract Full Text Full Text PDF PubMed Scopus (77) Google Scholar, 30Pandey A. Liu X. Dixon J.E. Di Fiore P.P. Dixit V.M. J. Biol. Chem. 1996; 271: 10607-10610Abstract Full Text Full Text PDF PubMed Scopus (77) Google Scholar, 31O'Neill T.J. Rose D.W. Pillay T.S. Hotta K. Olefsky J.M. Gustafson T.A. J. Biol. Chem. 1996; 271: 22506-22513Abstract Full Text Full Text PDF PubMed Scopus (128) Google Scholar, 32Liu F. Roth R. Proc. Natl. Acad. Sci. U. S. A. 1995; 92: 10287-10291Crossref PubMed Scopus (154) Google Scholar, 33He W. Rose D.W. Olefsky J.M. Gustafson T.A. J. Biol. Chem. 1998; 273: 6860-6867Abstract Full Text Full Text PDF PubMed Scopus (129) Google Scholar). These interactions have been proposed to play a role in the regulation of mitogenic signaling pathways. Interestingly, differential expression of Grb7 has been reported in some human cancers and tumor cell lines, suggesting a possible function in tumorigenesis (34Tanaka S. Mori M. Akiyoshi T. Tanaka Y. Mafune K. Wands J.R. Sugimachi K. Cancer Res. 1997; 57: 28-31PubMed Google Scholar, 35Tanaka S. Mori M. Akiyoshi T. Tanaka Y. Mafune K. Wands J.R. Sugimachi K. J. Clin. Invest. 1998; 102: 821-827Crossref PubMed Scopus (67) Google Scholar). The central domain of Grb7 family proteins is also called the GM (Grb and Mig) domain, which contains a region of >300 amino acids showing high sequence homology (approximately 50% amino acid identity) to a C. elegans gene product, Mig-10 (23Ooi J. Yajnik V. Immanuel D. Gordon M. Moskow J.J. Buchberg A.M. Margolis B. Oncogene. 1995; 10: 1621-1630PubMed Google Scholar, 26Stein D. Wu J. Fuqua S.A.W. Roonprapunt C. Yajnik V. D'Eustachio P. Moskow J.J. Buchberg A.M. Osborne C.K. Margolis B. EMBO J. 1994; 13: 1331-1340Crossref PubMed Scopus (220) Google Scholar, 36Manser J. Roonprapunt C. Margolis B. Dev. Biol. 1997; 184: 150-164Crossref PubMed Scopus (71) Google Scholar). The Mig-10 protein has been shown to play a role in long range migration of neuronal cells during embryonic development (37Manser J. Wood W.B. Dev. Genet. 1990; 11: 49-64Crossref PubMed Scopus (80) Google Scholar). This suggested a possible role for Grb7 in the regulation of migration of mammalian cells. Indeed, we have recently found that Grb7 could interact with FAK through its Tyr-397 in an adhesion-dependent manner and that overexpression of Grb7 stimulated cell migration (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar). In this report, we investigated the mechanisms by which Grb7 and its interaction with FAK regulate cell migration. We found that the SH2 domain of Grb7 plays a role in cell migration by mediating Grb7 localization to focal contacts through its interaction with FAK. We also identified Grb7 as a direct FAK substrate, and tyrosine phosphorylation of Grb7 by FAK is critical for its ability to increase cell migration. Last, we found that unlike Grb7 itself, several other Grb7 family members could not stimulate cell migration under similar experimental conditions, suggesting a possibly unique role for Grb7 in regulation of mammalian cell migration. Protein A-Sepharose 4B, glutathione-agarose beads, human plasma fibronectin, and the mouse monoclonal α-vinculin were purchased from Sigma. LipofectAMINE was purchased from Life Technologies, Inc. The mouse α-phosphotyrosine monoclonal antibody PY-20 was purchased from Transduction Laboratories (Lexington, KY). The rabbit polyclonal α-Grb7, α-Grb10, α-Grb14, and α-HA antibodies were obtained from Santa Cruz Biotechnology, Inc. (Santa Cruz, CA). The pEGFP-C3 plasmid encoding the green fluorescence protein (GFP) was as described (CLONTECH). Expression vectors encoding HA epitope-tagged Grb7 (pKH3-Grb7) and its SH2 domain (pKH3-Grb7.SH2) were described previously (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar). The Grb7 segment containing the Pro-GM domain was generated by polymerase chain reaction amplification using the forward (5′-GGAATTCATATGGAGCTGGATCTGTCTCCAC-3′) and reverse (5′-GGAATTCACGTCGACAGTTGGGTGCGGTGGA-3′) primers. The polymerase chain reaction product was digested with EcoRI and cloned into pKH3 at the corresponding site to generate pKH3-Pro-GM. Similarly, the GM segment of Grb7 was polymerase chain reaction amplified using the sense (5′-CGGAATTCATAAGGTGTACAGTGAGGATGGG-3′) and antisense (5′-GGAATTCACGTCGACAGTTGGGTGCGGTGGA-3′) oligonucleotides and inserted into pKH3 to generate pKH3-GM. The sequence containing the GM-SH2 segment was polymerase chain reaction-amplified using the sense (5′-CGGAATTCATAAGGTGTACAGTGAGGATGGG-3′) and antisense (5′-CGAATTCGGGCTGAGGCATGAGCCAG-3′) primers and inserted into pKH3 to generate pKH3-GM-SH2. The DNA segment encoding focal adhesion-targeting (FAT) sequences was excised from pBS-FAK with NruI andEcoRV digestion. This fragment was inserted into pEGFP-C3 at the SmaI site to generate pEGFP-FAT. The FAT segment was then cut out from pEGFP-FAT by SalI and EcoRI digestion. It was then inserted into pKH3-Pro-GM or pKH3-GM at the corresponding sites to generate pKH3-Pro-GM-FAT or pKH3-GM-FAT, respectively. Expression vectors encoding human Grb10α and Grb10γ (32Liu F. Roth R. Proc. Natl. Acad. Sci. U. S. A. 1995; 92: 10287-10291Crossref PubMed Scopus (154) Google Scholar, 38Dong L.Q. Du H. Porter S.G. Kolakowski Jr., L.F. Lee A.V. Mandarino J. Fan J. Yee D. Liu F. J. Biol. Chem. 1997; 272: 29104-29112Abstract Full Text Full Text PDF PubMed Scopus (66) Google Scholar) and Grb14 (24Daly R.J. Sanderson G.M. Janes P.W. Sutherland R.L. J. Biol. Chem. 1996; 271: 12502-12510Abstract Full Text Full Text PDF PubMed Scopus (105) Google Scholar) were generous gifts from Dr. F. Liu and Dr. R. Daly, respectively. CHO cells were maintained in F-12 medium plus 10% fetal bovine serum. SYF and control fibroblast cells (39Klinghoffer R.A. Sachsenmaier C. Cooper J.A. Soriano P. EMBO J. 1999; 18: 2459-2471Crossref PubMed Scopus (647) Google Scholar) were generous gifts from Drs. L. Cary, R. Klinghoffer, and P. Soriano and were maintained in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum. FAK−/− and the control FAK+/+ cells (20Ilic D. Furuta Y. Kanazawa S. Takeda N. Sobue K. Nakatsuji N. Nomura S. Fujimoto J. Okada M. Yamamoto T. Aizawa S. Nature. 1995; 377: 539-544Crossref PubMed Scopus (1591) Google Scholar) were generous gifts from Dr. D. Ilic and were maintained in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum. Transient transfections of CHO, SYF, FAK−/−, and control fibroblasts were performed using LipofectAMINE (Life Technologies, Inc.) according to the manufacturer's guidelines. Cells were transfected with a combination of pEGFP-C3 and expression vectors in a 1:5 ratio (3 μg of total DNA). Two days after transfection, the cells were trypsinized and washed in serum-free medium. Approximately 1 × 105 cells were then replated on a 60-mm tissue culture dish that had been coated with 5 μg/ml human plasma fibronectin in PBS. After a 2-h incubation at 37 °C and 5% CO2, the medium was replaced with a CO2-independent medium (Life Technologies, Inc.) supplemented with 0.1% fetal bovine serum, and the cells were transferred into a humidified 37 °C chamber at atmospheric CO2. A fluorescent image was captured to detect GFP+ (i.e. positively transfected) cells. Time lapse phase-contrast images were then captured at 15-min intervals using the Image-Pro Plus software program version 3.0 and its specific cell motility macro called OMAware (Image Acquisition and Object Motility Analysis) version 1.1 for Windows NT version 4.0. These phase-contrast images were converted to black and white images using OMAware and saved as JPEG images. The OMAware program was then used to determine the velocity, distance traveled, and migration path for each cell based on its centroid as determined from the cell boundaries in the JPEG images. The mean velocity of the control (GFP−) cells was determined and the velocity of each transfected cell (GFP+) was calculated relative to this value. Data were collected using approximately 30 positively transfected cells in three independent assays for each expression vector. For most experiments, subconfluent cells were washed twice with ice-cold PBS and then lysed with 1% Nonidet P-40 lysis buffer (20 mm Tris, pH 8.0, 137 mm NaCl, 1% Nonidet P40, 10% glycerol, 1 mm Na3VO4, 1 mmphenylmethylsulfonyl fluoride, 10 mg/ml aprotinin, and 20 mg/ml leupeptin). For some experiments, cell lysates were prepared from suspended cells, or cells that had been replated on fibronectin using ice-cold modified radioimmune precipitation buffer (50 mmTris, pH 7.4, 150 mm NaCl, 1% Triton X-100, 1% sodium deoxycholate, 0.1% SDS, 5 mm EDTA, 30 mmNa2HPO4, 50 mm NaF, 1 mm Na3VO4, 1 mmphenylmethylsulfonyl fluoride, 10 mg/ml aprotinin, and 20 mg/ml leupeptin), as described previously (40Guan J.L. Trevithick L.E. Hynes R.O. Cell Regul. 1991; 2: 951-964Crossref PubMed Scopus (474) Google Scholar, 41Guan J.-L. Shalloway D. Nature. 1992; 358: 690-692Crossref PubMed Scopus (726) Google Scholar). Lysates were cleared by centrifugation, and total protein concentration was determined using the Bio-Rad Protein Assay. Immunoprecipitations were carried out by incubating cell lysates with appropriate antibodies for 2 h at 4 °C, followed by incubation for 1.5 h with protein A-Sepharose. After washing, immune complexes were resolved using SDS-polyacrylamide gel electrophoresis. Western blotting was carried out using horseradish peroxidase-conjugated IgG as a secondary antibody and the Amersham Pharmacia Biotech ECL system for detection. Cells were processed for immunofluorescence staining as described with minor modification (40Guan J.L. Trevithick L.E. Hynes R.O. Cell Regul. 1991; 2: 951-964Crossref PubMed Scopus (474) Google Scholar). Cells were plated on 18-mm coverslips that had been coated with 10 μg/ml human plasma fibronectin. They were incubated in a 37 °C incubator to allow for cell attachment and spreading. Cells were then fixed with 3% formaldehyde for 15 min, washed three times with phosphate-buffered saline, permeabilized with 0.5% Triton X-100, and washed three times with phosphate-buffered saline. They were stained with primary antibodies (α-HA (1:300), α-vinculin (1:50)) in the presence of 10% goat serum for 1 h at room temperature. After washing three times with phosphate-buffered saline, the bound primary antibodies were detected with fluorescein isothiocyanate-conjugated anti-rabbit (1:300) and rhodamine-conjugated anti-mouse (1:150) antibodies, respectively. Image of stained cells was captured using an immunofluorescence microscope and a CCD camera. To investigate the mechanisms of stimulation of mammalian cell migration by Grb7, we constructed expression vectors encoding various fragments of Grb7 (Fig. 1 A). CHO cells were transiently transfected with these vectors. The expression of transfected Grb7 or its fragments were verified by Western blotting using anti-HA, which recognized the triple HA epitope tag fused to the N terminus of Grb7 or its fragments (Fig. 1 B). The effects of various Grb7 fragments on cell motility on fibronectin were then determined by using a time lapse imaging-based computerized motility analysis method (OMAware or Image Acquisition and Object Motility Analysis) as described under "Materials and Methods." Fig.1 C shows that, consistent with our previous results (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar), Grb7 stimulated CHO cell migration on fibronectin, whereas transfection of control pKH3 vector did not affect cell motility when compared with untransfected cells. Interestingly, expression of the Grb7 fragment containing the GM and SH2 domains also stimulated cell migration, suggesting that the Pro-rich segment at the N terminus was not necessary for Grb7 function in cell migration. However, expression of neither the GM domain nor the SH2 domain alone increased CHO cell migration. Indeed, the expression of the SH2 domain alone inhibited cell migration, as observed previously in NIH3T3 cells (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar). Expression of the fragment containing both the Pro-rich segment and GM domain also showed some inhibitory effect. These results suggested that the GM and SH2 domains of Grb7 function together to promote cell migration. Our previous studies have suggested a role for Grb7 binding to FAK via its SH2 domain in stimulation of cell migration (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar). Other studies have indicated the critical importance of focal contact localization of FAK in its cellular functions, including regulation of cell migration (19Gilmore A.P. Romer L.H. Mol. Biol. Cell. 1996; 7: 1209-1224Crossref PubMed Scopus (462) Google Scholar, 42Richardson A. Parson J.T. Nature. 1996; 380: 538-540Crossref PubMed Scopus (452) Google Scholar, 43Zhao J.-H Reiske H. Gian J.-L. J. Cell Biol. 1998; 143: 1997-2008Crossref PubMed Scopus (302) Google Scholar). Therefore, the Grb7 SH2 domain may be important for the function of Grb7 in cell migration by mediating Grb7 targeting to focal contacts through its association with FAK. To explore this possibility, we first analyzed the subcellular localization of Grb7 and its Pro-GM fragment lacking the SH2 domain. CHO cells were transfected with expression vectors encoding HA-tagged Grb7 or Pro-GM and were plated on fibronectin-coated coverslips. Immunofluorescence staining with anti-HA showed that Grb7 was localized in the cytoplasm as well as discrete regions of the plasma membrane resembling focal contacts (Fig.2 A, arrows). Staining of the same cells with anti-vinculin indicated its co-distribution with Grb7 in the focal contacts on the cell periphery (Fig. 2 B, arrows). In contrast, the Pro-GM fragment was detected only in the cytoplasm (Fig. 2, C andD). These results were consistent with our hypothesis that the Grb7 SH2 domain may be important for Grb7 function by mediating its binding to FAK and partial localization to focal contacts. To further investigate the above possibility, we generated a chimeric molecule (Pro-GM-FAT) that replaced the Grb7 SH2 domain with the FAT sequence from FAK (Fig.3 A). Double immunofluorescence staining for the chimeric molecule and vinculin confirmed their extensive co-localization in the cell peripheral and focal contacts, as expected (Fig. 2, E and F, arrows). The expression of transfected chimera molecules were also confirmed by Western blotting using anti-HA (Fig. 3 B). We then tested the effect of the chimeric molecule on cell motility in CHO cells. While either Pro-GM fragment (Fig. 1 C) or FAT alone (Fig.3 C) inhibited cell migration, expression of the chimeric protein composed of both segments increased cell migration significantly (Fig. 3 C). Similarly, another chimeric protein with the Grb7 GM domain fused to FAT also promoted cell migration, whereas the GM domain alone did not affect cell migration (Figs.1 B and 3 C). Taken together, these results suggested that the Grb7 SH2 domain was responsible for Grb7 localization in focal contacts through its binding to FAK, which may play an important role in stimulation of cell migration. To further explore the role of Grb7 interaction with FAK in the regulation of cell migration, we examined the possibility of tyrosine phosphorylation of Grb7 by FAK. CHO cells were co-transfected with pKH3-Grb7 encoding HA-tagged Grb7 and expression vectors encoding wild type, kinase-defective, or Tyr-397 to Phe mutant (Y397F) FAK. The cells were then lysed and immunoprecipitated with anti-Grb7 antibody followed by Western blotting with PY-20. As shown in Fig.4 A, Grb7 co-transfection with wild type FAK, but not the kinase-defective FAK (kd), resulted in a high level of tyrosine phosphorylation of Grb7. These results suggested that Grb7 might be a substrate for FAK. Interestingly, the Y397F mutant induced Grb7 phosphorylation to a lower level than the wild type FAK, suggesting that Grb7 association with FAK via Y397 (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar) may be required for efficient phosphorylation of Grb7 by FAK. Two other FAK associated proteins, paxillin and p130 cas, have been shown to be phosphorylated primarily by Src family kinases in the FAK-Src complex in a Tyr-397-dependent manner (17Vuori K. Hirai H. Aizawa S. Ruoslahti E. Mol. Cell. Biol. 1996; 16: 2606-2613Crossref PubMed Google Scholar, 44Schaller M.D. Hildebrand J.D. Parson J.T. Mol. Biol. Cell. 1999; 10: 3489-3505Crossref PubMed Scopus (183) Google Scholar). Therefore, an alternative explanation for a reduced phosphorylation by Tyr-397 mutant is that Grb7 is phosphorylated by Src family kinases rather than by (or in addition to) FAK. To assess this possibility directly, Grb7 was co-transfected with FAK into SYF cells lacking Src, Fyn, and Yes or control wild type cells (39Klinghoffer R.A. Sachsenmaier C. Cooper J.A. Soriano P. EMBO J. 1999; 18: 2459-2471Crossref PubMed Scopus (647) Google Scholar). Two days after transfection, cell lysates were prepared and immunoprecipitated with anti-Grb7 followed by Western blotting with PY-20. Fig. 4 Bshows that FAK induced Grb7 phosphorylation in both control and SYF cells (compare mock and FAK lanes), suggesting that Src family kinases were not involved in Grb7 phosphorylation by FAK. Furthermore, increased Grb7 phosphorylation was observed in the SYF cells compared with the control cells either with or without co-transfection of FAK (compare +/+ and −/− lanes). These results suggested that Grb7 is a direct substrate of FAK, whose phosphorylation is not dependent on the Src family kinases associated with FAK. To investigate potential function of Grb7 phosphorylation by FAK in cell migration, we first examined regulation of tyrosine phosphorylation of Grb7 by cell adhesion in FAK−/− and control FAK+/+ fibroblasts. Lysates were prepared from suspended cells or cells replated on fibronectins for 40 min. They were immunoprecipitated by anti-Grb7 and followed by Western blotting with PY-20 (Fig. 5). Consistent with our hypothesis that Grb7 is a direct substrate of FAK, no detectable tyrosine phosphorylation of Grb7 was observed in FAK−/− cells under either suspended or attached conditions. In control FAK+/+ fibroblasts, Grb7 exhibited an increased tyrosine phosphorylation upon cell adhesion to fibronectin. A similar increase in Grb7 phosphorylation was also observed in CHO cells used in most of our cell migration analysis. These results suggested that phosphorylation of Grb7 by FAK may play a role in cell migration. We also examined the subcellular localization of Grb7 and the chimeric molecule Pro-GM-FAT in FAK−/− cells. Cells were transfected with expression vectors encoding HA-tagged Grb7 or the chimeric molecule and were then plated on fibronectin-coated coverslips. Immunofluorescence staining with anti-HA showed Grb7 distribution in both the cytoplasm and membrane edges (Fig. 6 A). Co-staining with α-vinculin marked focal contacts. Inspection of both images as well as the merged image (data not shown) indicated a lack of co-localization of Grb7 with vinculin (Fig. 6, A andB), which is consistent with the idea that FAK is required for Grb7 (at least partial) localization in focal contacts. In contrast, HA-tagged Pro-GM-FAT chimeric protein showed extensive co-localization with vinculin in focal contacts in FAK−/− cells (Fig.6, C and D), indicating that the FAT sequence is sufficient for targeting molecules to focal contacts in the absence of endogenous FAK. Consistent with data in CHO cells (see Fig. 2,A and B), we also detected Grb7 co-localization with vinculin in focal contacts as well as the cytoplasm in FAK+/+ fibroblasts (Fig. 6, E and F), further supporting a role for FAK in Grb7 localization to focal contacts. To evaluate directly the role of Grb7 phosphorylation by FAK in cell migration, we examined the effects of Grb7 and the chimeric molecule Pro-GM-FAT on cell migration in FAK−/− cells. As reported previously (45Sieg D.J. Hauck C.R. Schlaepfer D.D. J. Cell Sci. 1999; 112: 2677-2691Crossref PubMed Google Scholar), transfection of FAK into these cells increased their migration on fibronectin (Fig. 7). Interestingly, expression of Grb7 did not stimulate cell migration but rather inhibited it. Furthermore, expression of the Pro-GM-FAT chimeric protein did not stimulate migration of the FAK−/− cells. Together with data in Fig. 3, these results demonstrated that Grb7 stimulation of cell migration is dependent on FAK expression. A lack of Grb7 phosphorylation in FAK−/− cells (see Fig. 5) is consistent with a role for Grb7 phosphorylation by FAK in cell migration. The inability of Pro-GM-FAT to stimulate cell migration despite its focal contact localization reinforced the potential critical importance of Grb7 phosphorylation by FAK in the regulation of cell migration. Several other Grb7 family members including Grb10α, Grb10γ, and Grb14 have been described, although their cellular functions are not totally understood at present (22Margolis B. Silvennoinen O. Comoglio F. Roonprapunt C. Skolnik E. Ullrich A. Schlessinger J. Proc. Natl. Acad. Sci. U. S. A. 1992; 89: 8894-8898Crossref PubMed Scopus (150) Google Scholar, 23Ooi J. Yajnik V. Immanuel D. Gordon M. Moskow J.J. Buchberg A.M. Margolis B. Oncogene. 1995; 10: 1621-1630PubMed Google Scholar, 24Daly R.J. Sanderson G.M. Janes P.W. Sutherland R.L. J. Biol. Chem. 1996; 271: 12502-12510Abstract Full Text Full Text PDF PubMed Scopus (105) Google Scholar, 25Frantz J.D. Giorgetti-Peraldi S. Ottinger E.A. Shoelson S.E. J. Biol. Chem. 1997; 272: 2659-2667Abstract Full Text Full Text PDF PubMed Scopus (101) Google Scholar). We investigated the possible role of these Grb7 family members in the regulation of cell migration using a similar assay. CHO cells were transiently transfected with expression vectors encoding Grb10α, Grb10γ, or Grb14 as well as Grb7 as a positive control. The expression of transfected Grb7, Grb10γ, and Grb14 were verified by Western blotting using appropriate antibodies (Fig.8 A). As expected, expression of Grb7 increased cell migration compared with cells transfected with vector alone (Fig. 8 B). However, we could not detect any stimulation of cell motility by Grb10α, Grb10γ, or Grb14 in these cells. They showed a slight inhibition of cell migration compared with untransfected or vector alone-transfected cells. Together, these results suggested that Grb7 may perform unique functions in mammalian cell migration among the related family members. Members of the Grb7 family adaptor proteins have been shown to bind a variety of other cellular signaling molecules. However, the functional significance of these interactions is largely unknown in the context of appropriate cellular processes. Recently, we have found that Grb7 interacted with FAK in an adhesion-dependent manner and that overexpression of Grb7 stimulated cell migration (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar). In this paper, we investigated the mechanisms of cell migration regulation by Grb7 interactions with FAK. We found that association of Grb7 with FAK via its SH2 domain was required for its localization to focal contacts and its ability to stimulate cell migration. We also identified Grb7 as a direct substrate of FAK and showed that Grb7 phosphorylation by FAK was necessary for stimulation of cell migration by Grb7. Formation of multiprotein complexes in the focal contacts has been proposed to be responsible for mediating integrin signaling pathways in regulation of various cellular functions (46Miyamoto S. Teremoto H. Coso O.A. Gutkind J.S. Burbelo P.D. Akiyama S.K. Yamamoto K.M. J. Cell Biol. 1995; 131: 791-805Crossref PubMed Scopus (1106) Google Scholar). Recent studies have shown that displacement of FAK from the focal contacts by its C-terminal FRNK segment inhibited integrin-FAK signaling pathways in the regulation of cell spreading, migration, and cell cycle progression (19Gilmore A.P. Romer L.H. Mol. Biol. Cell. 1996; 7: 1209-1224Crossref PubMed Scopus (462) Google Scholar, 42Richardson A. Parson J.T. Nature. 1996; 380: 538-540Crossref PubMed Scopus (452) Google Scholar, 43Zhao J.-H Reiske H. Gian J.-L. J. Cell Biol. 1998; 143: 1997-2008Crossref PubMed Scopus (302) Google Scholar). Interestingly, expression of a mislocalized FAK mutant competed with the endogenous FAK in focal contacts for binding other signaling molecules, which also functioned in a dominant negative manner to inhibit integrin-FAK signaling pathways in cell cycle regulation (43Zhao J.-H Reiske H. Gian J.-L. J. Cell Biol. 1998; 143: 1997-2008Crossref PubMed Scopus (302) Google Scholar). Thus, recruitment of signaling molecules to focal contacts by FAK may play an important role in triggering downstream pathways. The SH2 domain of Grb7 has been shown to mediate its binding to FAK (12Han D.C. Guan J.-L. J. Biol. Chem. 1999; 274: 24425-24430Abstract Full Text Full Text PDF PubMed Scopus (202) Google Scholar). A small fraction of wild type Grb7 was detected in the focal contacts, and deletion of the SH2 domain abolished this focal contact localization (Fig. 2). Deletion of the SH2 domain also abolished Grb7's ability to stimulate cell migration (Fig. 1). Furthermore, replacement of the SH2 domain by the FAT sequence targeted the chimeric molecule directly to focal contacts and also maintained its ability to stimulate cell migration (Figs. 2 and 3). Together, these data strongly suggested that recruitment of Grb7 to the focal contacts by FAK plays a critical role in triggering downstream pathways leading to cell migration. Furthermore, the observation that only a small fraction of Grb7 is co-localized with FAK suggests that Grb7 interaction with FAK may be dynamic and regulated. This is consistent with the findings that the same Tyr-397 site of FAK also interacts with other signaling including Src family kinases (6Xing Z. Chen H.-C. Nowlen J.K. Taylor S. Shalloway D. Guan J.-L Mol. Biol. Cell. 1994; 5: 413-421Crossref PubMed Scopus (285) Google Scholar, 7Cobb B.S. Schaller M.D. Leu T.-H. Parsons J.T. Mol. Cell. Biol. 1994; 14: 147-155Crossref PubMed Scopus (486) Google Scholar, 8Schaller M.D. Hildebrand J.D. Shannon J.D. Fox J.X. Vines R.R. Parsons J.T. Mol. Cell. Biol. 1994; 14: 1680-1688Crossref PubMed Scopus (1121) Google Scholar, 9Chan P.-Y. Kanner S.B. Whitney G. Aruffo A. J. Biol. Chem. 1994; 269: 20567-20574Abstract Full Text PDF PubMed Google Scholar), the p85 subunit of phosphatidylinositol 3-kinase (10Chen H.-C. Guan J.-L. Proc. Natl. Acad. Sci. U. S. A. 1994; 91: 10148-10152Crossref PubMed Scopus (478) Google Scholar), and phospholipase Cγ (11Zhang X. Chattopadhyay A. Ji Q.-S. Owen J.D. Ruest P.J. Carpenter G. Hanks S.K. Proc. Natl. Acad. Sci. U. S. A. 1999; 96: 9021-9026Crossref PubMed Scopus (158) Google Scholar). We also noted that while it did not promote cell migration, the Pro-GM segment of Grb7 actually inhibited it (Fig. 1). Without it being recruited to focal contacts by FAK, this fragment could interfere with either FAK-dependent or -independent signaling pathways in cell migration. Likewise, the full-length Grb7 also inhibited cell migration when it was not localized to focal contacts in FAK−/− cells (Fig. 7), which suggested an inhibition of the FAK-independent pathway. The mechanism by which Grb7 or its fragment affected such FAK-independent pathways in cell migration is unknown, although the Pro-rich sequences may be involved, since the GM domain only did not exhibit such activity in CHO cells (Fig. 1). Previous studies have shown that activation of FAK-mediated tyrosine phosphorylation of several other proteins including p130 cas and paxillin (15Turner C.E. Miller J. J. Cell Sci. 1994; 107: 1583-1591Crossref PubMed Google Scholar, 16Schaller M.D. Parsons J.T. Mol. Cell. Biol. 1995; 15: 2635-2645Crossref PubMed Scopus (502) Google Scholar, 17Vuori K. Hirai H. Aizawa S. Ruoslahti E. Mol. Cell. Biol. 1996; 16: 2606-2613Crossref PubMed Google Scholar, 18Schlaepfer D.D. Broome M.A. Hunter T. Mol. Cell. Biol. 1997; 17: 1702-1713Crossref PubMed Scopus (404) Google Scholar). However, tyrosine phosphorylation of p130 cas is primarily by Src family kinases in the FAK-Src complexes, and FAK served as a linker to bring p130 cas and Src together (17Vuori K. Hirai H. Aizawa S. Ruoslahti E. Mol. Cell. Biol. 1996; 16: 2606-2613Crossref PubMed Google Scholar). Similarly, paxillin could be tyrosine-phosphorylated when Src was co-expressed with catalytically defective FAK, suggesting that Src kinase is responsible for phosphorylation and FAK functioned to bring Src and paxillin together (44Schaller M.D. Hildebrand J.D. Parson J.T. Mol. Biol. Cell. 1999; 10: 3489-3505Crossref PubMed Scopus (183) Google Scholar). In contrast, several lines of evidence suggested that Grb7 is a direct substrate of FAK. First, tyrosine phosphorylation of Grb7 was induced by wild type FAK, but not by the kinase-defective FAK mutant (Fig. 4 A). Second, the absence of Src family kinases in the SYF cells did not prevent FAK-mediated Grb7 phosphorylation but rather enhanced it (Fig. 4 B). Third, tyrosine phosphorylation of Grb7 was also increased by cell adhesion to fibronectin, which was known to induce FAK activation (Fig.5). Finally, no Grb7 phosphorylation could be detected in FAK−/− cells even after cell adhesion (Fig. 5), which had been shown to activate the Src kinases in these cells (47Sieg D.J. Ilic D. Jones K.C. Damsky C.H. Hunter T. Schlaepfer D.D. EMBO J. 1998; 17: 5933-5947Crossref PubMed Scopus (289) Google Scholar). It will be interesting to determine the sites phosphorylated on Grb7 by FAK, which may suggest other potential direct FAK substrates. It is interesting to note that Grb7 exhibited increased tyrosine phosphorylation by FAK in SYF cells compared with the control fibroblasts (Fig. 4 B). It is possible that Src family kinases binding to FAK at Tyr-397 could compete with Grb7 binding to FAK at the same site in normal cells. Therefore, the absence of Src family kinases in SYF cells would allow an increased Grb7 binding (or at least access) to FAK, leading to the very strong tyrosine phosphorylation of Grb7. Alternatively, Grb7 may bind to other intracellular signaling molecules in an Src-dependent manner in normal cells. The absence of Src family kinases in SYF cells could release the associated Grb7, allowing its increased interaction with and phosphorylation by FAK. Future studies will be necessary to determine these interesting possibilities. Our results showed that the Y397F FAK mutant was not as effective as wild type FAK in inducing Grb7 phosphorylation, suggesting that Grb7 association with FAK may facilitate its phosphorylation by FAK. However, the Y397F mutant clearly phosphorylated Grb7 (Fig. 4), indicating that association is not absolutely required. It is possible that co-localization of Grb7 with FAK at focal contacts (even without direct association) may increase the efficiency of Grb7 phosphorylation by FAK. Thus, Grb7 could be recruited into focal contacts by endogenous FAK and phosphorylated by both endogenous FAK and the overexpressed exogenous Y397F FAK mutant. These data suggested that Grb7 association with FAK as well as its focal contact recruitment by FAK may be important factors for Grb7 phosphorylation by FAK, although the precise mechanism of Grb7 phosphorylation by FAK will await further investigation. The functional significance of Grb7 phosphorylation by FAK is not well understood at present. A lack of tyrosine phosphorylation of Grb7 in FAK−/− cells correlated with its inability to stimulate cell migration in these cells. Furthermore, expression of the Pro-GM-FAT chimeric molecule failed to stimulate migration of FAK−/− cells, while it readily increased migration of FAK+/+ CHO cells. Subcellular localization studies indicated that the chimeric molecule was targeted to focal contacts in both cell types. Therefore, tyrosine phosphorylation of Grb7 may be necessary for its stimulation of cell migration. Alternatively, stimulation of cell migration by Grb7 may be dependent on other signaling pathways downstream of FAK (e.g. FAK/phosphatidylinositol 3-kinase association (48Reiske H.R. Kao S.-C. Cary L.A. Guan J.-L. Lai J.-F. Chen H.-C. J. Biol. Chem. 1999; 274: 12361-12366Abstract Full Text Full Text PDF PubMed Scopus (235) Google Scholar)), which are defective in the FAK−/− cells. This is consistent with the idea that FAK could trigger multiple downstream signaling pathways, which regulate cell migration in a coordinated manner. It remains a future challenge to delineate the spatial and temporal regulations of FAK complexes with other signaling molecules in triggering multiple pathways in cell migration. We are grateful to Dr. F. Liu of University of Texas Health Science Center at San Antonio for plasmids encoding Grb10α and Grb10γ and Dr. R. Daly of the Garvan Institute for plasmid encoding Grb14. We thank Drs. D. Ilic and C. Damsky (University of California, San Francisco) for FAK−/− and control cells and Drs. L. Cary, R. Klinghoffer, and P. Soriano of Fred Hutchinson Cancer Research Center for the SYF cells. We thank Renee Christopher, Ji-He Zhao, Hiroki Ueda, Heinz Reiske, and Smita Abbi for critical reading of the manuscript and helpful comments.